Radio-over-fibre for generation and transmission 32-tupling frequency optical millimeter wave with polarization modulators - Chen, Xinqiao; Dai, Siyuan; Liu, Xiaorui; Li, Zhihan; Chen, Xu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
A novel structure to generate 32-tupling frequency millimeter-wave (MMW) signal using polarization modulators (PolM) is proposed. The ±16th order sidebands are generated by the 16th order sidebands generator which is mainly constructed by six PolMs and beat in a photodetector for generating the 32-tupling frequency MMW. The optical sideband suppression ratio (OSSR) of the generated ±16th order sidebands are 29.89 and 29.7 dB from theoretical analysis and simulation. The radio frequency (RF) spurious suppression ratio (RFSSR) of the obtained 32-tupling frequency MMW are 23.88 and 23.32 dB from theoretical analysis and simulation. A radio over fiber (ROF) system to transmit the generated 32-tupling frequency MMW is built. In the center station, the +16th order sideband from the ±16th order sideband generator is filtered out by a filter, after the downlink data is modulated on it. It is recombined with –16th order sideband and transmitted to the based station over fiber. In the based station, a part of –16th order sideband is reflected by a fiber Bragg grating (FBG), and the uplink data is modulated on it and transmitted to the center station over fiber. The signal emerging from the FBG is injected into the photodetector and the 32-tupling frequency MMW with downlink data is generated. The simulation results show that for the transmission fiber length 30 km, the bit-error-rate (BER) is less than 10–9, the power cost of the uplink and downlink is less than 0.44 and 0.5 dB, respectively.
Optica Applicata, Vol. 54, 2024, nr 1, s. 51-67
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; radio-over-fiber (ROF); millimeter-wave (MMW); polarization modulator (PolM); Mach–Zehnder interferometer (MZI); optical sideband suppression ratio (OSSR); radio frequency spurious suppression ratio (RFSSR)